Association of dietary fiber and risk of hip fracture in men from the Framingham Osteoporosis Study and the Concord Health and Ageing in Men Project. Issue 2 (June 2022) - Dai, Zhaoli; Hirani, Vasant; Sahni, Shivani; Felson, David T.; Naganathan, Vasi; Blyth, Fiona; Le Couteur, David; Handelsman, David; Seibel, Markus J; Waite, Louise; Kiel, Douglas P; Cumming, Robert
Background: Data in the Offspring Framingham Osteoporosis Study (FOS) suggested that higher intake of dietary fiber was modestly protective against loss of bone mineral density at the femoral neck in men but not in women. Aim: To examine the relationship of fiber intake with risk of hip fractures in men. Methods: We included 367 men from the FOS Original cohort, 1730 men from the FOS Offspring cohort, and 782 men from the Concord Health and Ageing in Men Project (CHAMP) in the analysis. Incident fractures were defined as medically confirmed first occurrence of osteoporotic fractures at the proximal femur. Fiber intake was estimated via a validated food frequency questionnaire (FFQ) or diet history. Cox proportional hazards models were applied to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). A random-effects model was used to estimate the pooled relative risk in meta-analysis. Results: Seventy-two incident hip fractures were identified, of which 24 occurred in the FOS Original cohort [mean (SD): age 75.3 (5.1) years; follow-up time: 8.5 (6.2) years; dietary fiber: 19 (8) (g/d)], 19 in the FOS Offspring cohort [58.8 (9.8) years; 11.0 (5.9) years; 19 (8) (g/d)], and 29 in CHAMP [81.4 (4.5) years; 5.2 (1.5) years; 28 (10) (g/d)]. We did not find significant associations within each cohort between fiber intake and risk of hip fractures. The pooled HR (95% CI) was 0.80 (0.39, 1.66) comparing energy-adjusted dietary fiber at tertile 3 vs. tertile 1 (I 2 = 0, p = 0.56). Conclusion: These data suggested that dietary fiber was not associated with risk of incident hip fractures in men.